Identification and field evaluation of a new blend of the sex pheromone of Hypsipyla grandella - Blassioli Moraes, Maria Carolina; Borges, Miguel; Laumann, Raul Alberto; Borges, Rafael; Viana, Amanda Rodrigues; Thomazini, Marcílio José; Silva, Cleonor Cavalcante Alves; de Oliveira, Márcio Wandré Morais; Boff, Mari Ines Carissimi (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to identify and carry out a field testing of the sex pheromone composition of the mahogany shoot borer, Hypsipyla grandella, from a population in Southern Brazil. Abdominal glands of H. grandella females were excised and extracted using n-hexane; the gland extracts were analysed by gas chromatography (GC-FID and GC-MS). Wind-tunnel and electrophysiology experiments were conducted to evaluate the role of gland compounds in the mating behavior of H. grandella males. In the field, pheromone traps containing the identified pheromone were tested. In addition to the two previously identified compounds – (9Z,12E)-tetradecadien-1-ol and 9Z,12E)‑tetradecadienyl acetate –, in insects from Central America populations, two additional compounds were identified in the blend: (9Z)- tetradecen-1-ol and (9Z)-tetradecenyl acetate. Gas chromatography-electroantennographic analyses showed that these four components elicited antennal responses from conspecific males. Wind tunnel bioassays using different amounts of the components Z9‑14:OH, Z9,E12‑14:OH, Z9‑14:OAc, and Z9,E12‑14:OAc, elicited male responses similar to the response to conspecific calling females. When the binary and quaternary mixtures were tested in field conditions, males were attracted to the traps containing the quaternary mixture. The new pheromone blend identified in H. grandella males has a great potential to be exploited as a monitoring tool or control measure in the field.